The effects of weather factors and altitude on physical and technical performance in professional soccer: A systematic review - Illmer, S.; Daumann, F. (Journal of Science and Medicine in Sport Plus, 2022)
Soccer, as the most popular sport in the world, is characterized by complex performance requirements and is influenced by many external factors. In order to record and systematize the scientific findings of the effects of weather factors and altitude on physical and technical performance in professional male and female soccer a systematic literature search was conducted in the relevant databases from 8th to 15th of February 2022. From 2.396 records, 150 were selected for detailed screening. 21 studies were included in this review that met the following inclusion criteria: professional male or female soccer players over 18 years of age; field study under real-life conditions; effects on physical and/or technical performance, influence of at least one weather-related factor. The selected articles considered different research objects, periods of time, technologies, or methods. Most publications investigated the factors of temperature, humidity and altitude and showed some significant effects on physical performance, while technical performance often did not change significantly. For all analysed environmental factors, it can be summarized that in different environmental conditions, professional soccer players may consciously adjust certain performance parameters to maintain key match characteristics throughout the whole game. This pacing strategy allows them to keep the influence of environmental factors in check as far as possible.